Recommendations for the assessment and forecast of shore deformations in the average flow of the Amudarya river - Norkulov Bekhzod; Nazaraliev Dilshod; Raimova Iqboloy; Vafoeva Ozoda (E3S Web of Conferences, 2023)
The paper presents the results of the field and numerical studies of the bank destruction in the middle section of the Amudarya River. The article presents the main factors of destruction of the banks during floods and low water flow. In addition, recommendations for protecting the coast from erosion are also developed. As a result of research into the process of intensive local reshaping of an easily eroded channel, hydraulic schemes have been developed for the occurrence of local bank erosion both in steady and unsteady motion in an open stream. The recommendations are based on some patterns of interaction between the river channel and the flow during the period of low water and high-water flow. The external manifestation of this interaction is the coastal deformations, leading to the planned displacement of the channel.